1998
DOI: 10.1046/j.1365-201x.1998.0318e.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in serum vascular endothelial growth factor levels during altitude training

Abstract: The present study was performed to evaluate the effects of physical exercise at altitudes on serum vascular endothelial growth factor (VEGF) levels. Eight subjects underwent intensive swimming training for 21 days at 1886 m. After altitude training commenced, red blood cell (RBC) counts and erythropoietin levels increased, but both haemoglobin and haematocrit levels did not change significantly. The serum level of VEGF, measured by means of a highly sensitive chemiluminescence (ELISA), showed a transient decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 18 publications
4
50
0
Order By: Relevance
“…7 Asano et al reported increased serum VEGF levels in athletes who trained at high altitudes and that their serum VEGF levels returned to normal 1 month after returning to sea level. 19 However, the mechanism that leads to the overexpression of myocardial microvessels in patients with C-CHD is unknown, nor is the relationship between VEGF and microvessel formation in the myocardium completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…7 Asano et al reported increased serum VEGF levels in athletes who trained at high altitudes and that their serum VEGF levels returned to normal 1 month after returning to sea level. 19 However, the mechanism that leads to the overexpression of myocardial microvessels in patients with C-CHD is unknown, nor is the relationship between VEGF and microvessel formation in the myocardium completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have shown that the availability of BDNF deficiency is associated with vulnerability to depression [153]. Exercise training therefore compensates the atrophic changes of the hippocampus for its impact on the expression of neurotrophic growth factors, which have an antidepressant action similar to that hypothesized for the treatment of antidepressant drugs [127,130,[154][155][156][157]. Thus, there is support for the neurotrophic hypothesis of depression as an alternative to any other hypothesis.…”
Section: Neurobiological Mechanismsmentioning
confidence: 85%
“…There is evidence that the practice of exercise causes physiological changes in monoamine levels in rats [122], as well as in healthy men and women [123], alters the levels of cortisol in rats and healthy individuals [123][124][125][126] and leads to adaptations in limbic structures that have been implicated in depression, in addition to increased expression of neurotrophic factors in hippocampus of rats and healthy subjects [121,[125][126][127][128][129][130][131]. However, no evidence was obtained in depressed patients.…”
Section: Neurobiological Mechanismsmentioning
confidence: 99%
“…The physiological mechanisms are the following: 1) increase in the pulmonary ventilation 39 ; 2) reduction in the HR previously increased in the acute response 22,39 ; 3) decrease in the plasmatic volume 39,40 ; 4) reduction of the accumulation of lactate in the blood during submaximal exercise in relation to the more elevated levels of acute response 39 ; 5) improvement of the cardiorespiratory capacity for exercise, also related to the initial exposure to the hypobaric hypoxia 23,41 ; 6) increase in the secretion of renal erythropoietin, in the hemoglobin mass and in the hematocrit 34,36,37,42 .…”
Section: Acclimatizationmentioning
confidence: 99%
“…Erythropoietin -A few hours after exposure to hypobaric hypoxia, the secretion of renal erythropoietin increases [34][35][36][37] . As it stimulates the synthesis of red blood cells, in approximately one week it significantly increases the concentration of hemoglobin and, therefore, the capacity of transporting O 2 in the blood 38 .…”
Section: Endothelial and Blood Alterations -Endothelinmentioning
confidence: 99%